A throughput model for CSMA/CA with a cross-layer payload-dropping optimization - Lau, Chiew Tong (2013)
In this paper, we formulate the throughput of a spatially-optimized CSMA/CA in two interference-limited co-channel cells, and validate it using statistics obtained via simulation. This special variant of the protocol incorporates a MAC/PHY cross-layer mechanism which aborts the reception of the payload portions of frames from co-channel cells in interference-limited multi-cell deployments. For physical transceivers relying solely on preamble detection for carrier sensing, this optimization adequately mitigates the exposed node syndrome, thereby allowing nodes to enjoy nearly the maximum throughput as provided by CSMA/CA in single cell or carrier-sensing threshold (CST) isolated scenarios.